TAXING GLOBAL DIGITAL COMMERCE. - COCKFIELD, ARTHUR. HELLERSTEIN, WALTER. LAMENSCH, MARIE (KLUWER LAW INTERNATIONAL, 2019)
Taxing Global Digital Commerce' studies the tax challenges presented by cross-border digital commerce and reports on the rapidly changing environment surrounding the challenges. Digital commerce - the use of computer networks to facilitate transactions involving the production, distribution, sale, and delivery of goods and services - has grown from merely streamlining relations between consumer and business to a much more robust phenomenon embracing efficient business processes within a firm and between firms. Inevitably, the related taxation issues have grown as well. This latest edition of the preeminent text on the taxation of digital transactions revises, updates and expands the book?s coverage that reflects the significant changes that had been made to the content of the earlier volumes. It includes a detailed and up-to-date analysis of income tax and VAT developments regarding digital commerce under the Organisation for Economic Co-operation and Development and G20 Base Erosion and Profit Shifting (BEPS) reforms. It then explores the new EU VAT rules for both tangible and intangible Internet supplies and the implications of digital commerce for US state retail sales and use tax regimes, taking account of the significant developments resulting from the 2018 US Supreme Court decision in 'Wayfair'.